An Assessment of High Density Energy Plantations (HDEP) in Gujarat on Silvicultural, Ecological, Management and Economic Aspects - Gogate, M. G. (Indian Forester, 1983)
Practice of planting forest tree species, particularly eucalypts, more density, which is termed as "High Density Energy Plantations (HDEP)", is based on the assumption that the factors defining maximum returns/density of planting are the availability of soil nutrients, sunlight and water. Under tropical conditions wherein sunlight is ample, with adequate water and soil nutrients, through application of irrigation and ferlilizers, 5 to 6 times more yield per unit area is expected. Density of planting, however, is governed by number of other factors viz. availability and economics of inputs like irrigation, fertilisers, growth hormones, insecticides, managerial skills, industrial base for utilisation of outputs, feasibility of diverting land and ground water resources which are immensely suitable for agriculture to forestry tree crops etc. Projected Cost/benefits apparently show very attractive net returns and thus practice is gaining popularity. These projections do not, however stand close scrutiny and thus blind following of the practice is not advocated. Short and long rang impacts of intensive Euaclyptus tree crop management under semi-arid conditions are highlighted. A need for evolving appropriate technology packages to ensure optimum sustained yield under different agro-climatic edaphic conditions and providing basic nutrient requirements is indicated. In view of its long range impacts on the ecology, there is need for moderation in providing surh inputs. Approach of dense planting with high inputs is a step in right direction however, in view of its economic and policy implications the whole issue deed be carefully examined.